Los instrumentos especializados del consejo de la judicatura para casos de violencia sexual de niños, niñas y adolescentes - Cadena, Alexis A. (2023)
Both legally and doctrinally, systems have been established to protect the rights of children and adolescents, which is why it is important for this vulnerable group to be aware of them. Based on this, the present work was aimed at analyzing the adoption of specialized instruments of the Ecuadorian Judiciary Council for sexual violence committed against children and adolescents. It was based on the qualitative approach, type of descriptive analytical research, with application of the analytical-critical method. Based on the application of an interview guide to judges, prosecutors and lawyers, it was concluded that the Judiciary Council has issued specialized instruments for sexual violence against children and adolescents, although their application is still insufficient. These seek to provide an effective response to these crimes, but face limitations due to lack of dissemination, training and resources. It was recommended to harmonize national laws with international standards for children's rights, encourage the participation of children in court proceedings, improve the training of judicial operators, promote awareness campaigns against child sexual violence and allocate resources for the effective implementation of specialized legal instruments.